The therapeutic relationship in EMDR therapy—A survey - Hase, Michael; Brisch, Karl Heinz; Solomon, Roger M.; Hase, Adrian (Frontiers in Psychology, 2025)
The history of EMDR therapy goes back to 1987, when it was introduced as EMD, a novel treatment for PTSD by Francine Shapiro. Over the course of time EMD developed into the comprehensive therapy approach named EMDR therapy. The development of the Adaptive Information Processing (AIP) Model, the model of pathogenesis and change of EMDR therapy, was a milestone in this development from technique to psychotherapy approach. Lately a description of the therapeutic relationship in EMDR therapy has been proposed based on attachment theory. The therapeutic relationship has been described as a core element of EMDR Therapy, and seems to be related to the structure of EMDR Therapy. An internet-based survey of EMDR therapists in several waves was used to evaluate whether EMDR therapists support the above mentioned description of the therapeutic relationship in EMDR therapy. The self-experience of the EMDR therapists in EMDR therapy as elicited in the survey seems to support the description of the therapeutic relationship in EMDR therapy. Even if the survey was only conducted with EMDR therapists, thus limiting the informative value on the patient population in general, it offers valuable insights into the therapeutic relationship in EMDR Therapy. Implications for treatment, training and research will be discussed.